Child Abuse or Bleeding Disorder—An Interdisciplinary Approach - Knöfler, Ralf; Streif, Werner; Watzer-Herberth, Irmina; Hahn, Gabriele; Schmidt, Uwe (Hämostaseologie, 2019)
Children with an unexplained bleeding tendency are frequently referred to a haemostaseologist for further evaluation. Careful standardized history taking and clinical evaluation should allow for distinguishing bleeds after minor injury and trauma which are very common in all children. However, in two groups of children bleeding symptoms may be more significant than expected: those with an underlying coagulation disorder and those who have been subjected to physical child abuse. The coexistence of child abuse and a bleeding disorder must always be considered. An extended coagulation diagnostic is required if the morphology of bleedings is not clearly suspicious for child abuse and in the absence of typical concomitant injuries, e.g., bone fractures. An interdisciplinary approach involving a forensic pathologist and a paediatric haemostaseologist for assessment of bleeding symptoms, the explanation of the clinical findings, and the critical evaluation of laboratory results are essential in such cases. This review is focussed on symptoms in accidental and nonaccidental injuries in children assisting haemostaseologists in decision making in cases of child protection issues.
Keywords: child abuse; injuries; bleeding symptoms; haemostasis testing